Development of Experiential Learning Discovery Learning Tools Through E-learning on Protist Material - Fatikhatun Nikmatus Sholihah; Sofi Aristya Hanifa (APPLICATION: Applied science in Learning Research, 2021)
Using the discovery learning concept, this study intends to generate learning resources such as lesson plans, LKPD, and learning outcomes tests. Research and development (R&D) methodologies are used in this work. The design research and development R&D procedure is referred to as the implementation procedure. The R&D model has ten stages: 1) potential and problems,) Product Design, 3) Data Collection, 4) Design Validation, 5) Design Revision, 6) Product Trial, 7) Product Revision, 8) Trial Use, 9) Product Revision, and 10) Mass Production. Due to a complete lack of time and research funds, this study only made it to the design revision stage. A material validation questionnaire was utilized for validator 1 and a learning device validation questionnaire was used for validator 2. Based on the findings of the research and discussion, it can be concluded that an experience-based Discovery Learning learning tool has been produced through E-learning as a learning tool that has been assessed by several validators, with an average value of 97.3 for lesson plans with a very feasible category for validators 1 and 78.6 with eligible categories for validator 2. The average LKPD score is 94.3 for validator 1, with a very good category, and 81.4 for validator 2, with a very feasible category. The average value for the learning outcomes test is 95 for validator 1, with a very good category, and 87.5 for validator 2, with a very feasible category.